2017
DOI: 10.1016/j.vetimm.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting induction of peripheral IFN-γ recall response to influenza A virus vaccination in pigs

Abstract: While T cell contribution to IAV immunity is appreciated, data comparing methods to evaluate IFN-γ production by IAV-specific T cells elicited following vaccination is limited. To understand the differential immunogenicity between live-attenuated influenza virus (LAIV) and whole-inactivated virus (WIV) vaccines in relation to induction of peripheral T cell responses, ELISpot and ELISA were used to assess IFN-γ production by peripheral lymphocytes following antigen restimulation. Following restimulation, periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Babraham's pigs were used as model to identify T cells epitopes because their syngeneic MHC loci which aids identification of SLA restriction of the identified epitopes. Previous studies demonstrated that immunization strategies based on the administration of whole inactive virus (WIV) formulated with adjuvant in pigs were able to produce an IFNγ or proliferative cell mediated response in peripheral blood involving T helper subsets (8,16,24). Moreover, the generated immunity was also able to respond to heterologous IAV strains (24).…”
Section: Discussionmentioning
confidence: 99%
“…Babraham's pigs were used as model to identify T cells epitopes because their syngeneic MHC loci which aids identification of SLA restriction of the identified epitopes. Previous studies demonstrated that immunization strategies based on the administration of whole inactive virus (WIV) formulated with adjuvant in pigs were able to produce an IFNγ or proliferative cell mediated response in peripheral blood involving T helper subsets (8,16,24). Moreover, the generated immunity was also able to respond to heterologous IAV strains (24).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately prior to euthanasia, ∼8 mL of whole blood was collected from each animal into a sodium citrate cell-preparation tube (CPT; BD Biosciences). Samples were transported to the lab at RT and processed using manufacturer's recommendations as previously described (42). HBSS was used to wash and resuspend cells.…”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Isolationmentioning
confidence: 99%
“…This significantly complicates the quick data collection necessary to make an effective vaccine; therefore, vaccination can rarely protect people. (12)(13)(14) Another challenge is that alongside the influenza viruses, so-called «imitators» (the viruses of parainfluenza, adenoviruses, respiratory syncytial virus (RSV), coronavirus, etc.) could be a reason for acute respiratory tract disease.…”
Section: Introductionmentioning
confidence: 99%